2009
DOI: 10.1007/s12185-009-0465-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of matched sibling and alternative donor stem cell transplantation for 26 children with severe aplastic anemia

Abstract: In this study, we reported the outcomes of hematopoietic stem cell transplantation (HSCT) as a treatment modality for pediatric patients admitted over the past 20 years in a single institute. From January 1989 to January 2007, 26 patients with a median age of 8 years underwent 14 matched sibling donor (MSD) and 12 alternative donor (AD) transplantations. Two patients received second transplantation successfully after primary graft failure and late graft rejection. Two patients who received transplantation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…The same GvHD prophylaxis was given to the majority of children. In contrast to the other reports (Hsieh et al 2010;Yagasaki et al 2010), in our study children transplanted from MUD demonstrated, when compared to those transplanted from MSD, the same time of neutrophil engraftment and faster platelet engraftment. This may be related to CD34 cells source, i.e., two-thirds of children undergoing MUD-HSCT received stem cells from peripheral blood, while those transplanted from MSD almost exclusively from BM and to a higher CD34 cells dose used in the case of MUD-HSCT.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The same GvHD prophylaxis was given to the majority of children. In contrast to the other reports (Hsieh et al 2010;Yagasaki et al 2010), in our study children transplanted from MUD demonstrated, when compared to those transplanted from MSD, the same time of neutrophil engraftment and faster platelet engraftment. This may be related to CD34 cells source, i.e., two-thirds of children undergoing MUD-HSCT received stem cells from peripheral blood, while those transplanted from MSD almost exclusively from BM and to a higher CD34 cells dose used in the case of MUD-HSCT.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the reported groups of children were usually small with unrelated donors typed at the various resolution levels and conditioned with different preparative regimens, mostly containing low-dose total body irradiation (LD-TBI), which is not advocated in children (Führer 2008). Only two reports compared results of MSD-HSCT and MUD-HSCT in children with SAA, and in both studies children transplanted from MUD received TBI (Hsieh et al 2010;Yagasaki et al 2010). There is another comparative report (Kennedy-Nasser et al 2006), but the cohort of 23 alternative donors was very heterogenous, and again LD-TBI was given within preparative regimen.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that another important finding derived from our cohort of both MSD and UD transplants conditioned with the same regimen is the similar OS observed between MSD and UD transplant recipients. Comparable outcomes for these two modes of treatment in children with SAA have been reported before , with one recent study suggesting that matched UD transplant is a valid second option when an MSD is not available, considering the low response of patients to rabbit ATG in their study . The results of our cohort also contribute to accumulating evidence for the feasibility of UD transplant as the next therapeutic option after MSD transplant in children, especially in situations where rapid identification of a UD is possible.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, updated EBMT reports showed an excellent 83% 5‐year actuarial survival rate for AD HSCT performed after 2004, even when adult patients were included; 92% 5‐year actuarial survival was observed if patients received transplant within 2 years of diagnosis (Bacigalupo et al , ). Many centres reported similar outcomes between MSD and MUD HSCT for children with SAA (Kennedy‐Nasser et al , ; Yagasaki et al , ; Samarasinghe et al , ; Hsieh et al , ). Thus, Meyers and Maziarz () suggested an early application of MUD HSCT for SAA.…”
Section: Discussionmentioning
confidence: 91%